Pola Asuh Permisif Ibu dan Perilaku Merokok Pada Remaja Laki-Laki di Sma Negeri 1 Semarapura - Sanjiwani, Ni Luh Putu Yuni; Budisetyani, I Gusti Ayu Putu Wulan (Jurnal Psikologi Udayana; Vol 1 No 2 (2014), 2014)
Indonesia placed the 4th rank in the highest number of smokers in the world which consisted of not only adults but also adolescents. There are several things that influence adolescent smoking behavior, namely parenting style, peers, personality factors, and also advertisements. Parenting style which will be investigated in this research has three forms namely democratic, authoritarian, and permissive. Permissive parenting style is one form of parenting style which is presumably associated with smoking behavior. Permissive parenting style has characteristics as no child guiding, agreeing child's behavior, and do not use punishment, thus making the child feels brave in doing maladaptive behaviors such as smoking. Since the prevalence of smoking behavior among men is bigger, the researcher wanted to see whether there is a relationship between permissive parenting style of mother and smoking behavior of male adolescents in SMA Negeri 1 Semarapura.   Subjects in this research are 75 male students in SMA Negeri 1 Semarapura. Research method uses correlational study. Data are collected with questionnaires. Permissive parenting style of mother questionnaire has 16 valid items and its reliability coefficient is 0,916 which means the questionnaire is reliable since its reliability coefficient is higher than minimum standard 0,600. Smoking behavior questionnaire has 20 valid items and its reliability coefficient is 0,906 which means the questionnaire is reliable since its reliability coefficient is higher than minimum standard 0,600. Result of assumption test shows data are normal and linear. Linearity test between permissive parenting style of mother and smoking behavior has significance level 0,000 which means linear since its significance level is lower than 0,05. Result of this research finds positive significant relationship between permissive parenting style of mother and smoking behavior and its correlational coefficient is 0,493. The value of coefficient of determination is 0,243 which shows permissive parenting style  of mother has 24,3% contribution to smoking behavior.   Keywords: permissive parenting style, smoking behavior, male adolescents.